EXPLORING CULINARY IDENTITY: A GASTRO-CRITICAL ANALYSIS OF AHMAD TOHARI'S RONGGENG DUKUH PARUK AND SURABANGLUS - Widya Nirmalawati; Dodi Siraj Muamar Zain; Khristianto Khristianto (University of Kuningan, 2024)
The novel Ronggeng Dukuh Paruk and the short story Surabanglus are two works by Ahmad Tohari (AT) that talk about food and how food becomes the identity of a society. RDP tells the story of how Srintil, the Ronggeng Dukuh Paruk, loses her parents due to a massive poisoning in her village caused by tempeh bongrek made by her parents. With very little knowledge of toxicology, the people of Dukuh Paruk